Iron single atom enzyme-mediated hydrogen sulfide delivery amplifies reactive oxygen species cascade to induce ferroptosis susceptibility - Xuegang Niu; Penghui Wei; Mingtao Zhu; Hongjia Zheng; Dezhi Kang; Qianxi Chen; Fuxiang Chen; Yiping Li; Rong Xie; Yang Zhu; Dengliang Wang (Materials Today Bio)
Lipid peroxidation (LPO) represents one of the most deleterious processes contributing to ferroptosis susceptibility. However, the tumor microenvironment is often characterized by an overproduction of endogenous glutathione (GSH) and reactive oxygen species (ROS)-scavenging enzymes, which limit the ferroptosis susceptibility. Herein, we introduce an iron single-atom enzyme (Fe/SAE) nanoplatform, termed Fe/SAE@A, that acts as hydrogen sulfide (H2S) donor anethole trithione (ADT) delivery system to amplify LPO-mediated ferroptosis vulnerability. Upon internalization by cancer cells, Fe/SAE, featuring atomically dispersed active metal sites, exhibits remarkable peroxidase-mimicking activity, converting hydrogen peroxide (H2O2) into hydroxyl radicals. Furthermore, Fe/SAE@A facilitates the release of ADT, delivering H2S to significantly inhibit ROS-scavenging enzymes, which results in elevated intracellular H2O2 levels. This, in turn, initiates a robust Fe/SAE-catalyzed ROS cascade within cancer cells, driving irreversible LPO. Additionally, Fe/SAE@A exhibits glutathione oxidase-mimicking activity, efficiently oxidizing reductive GSH to glutathione disulfide, thereby promoting the inactivation of glutathione peroxidase 4. These results confirm the mechanistic basis of ferroptosis induced by Fe/SAE@A, underscoring remarkable capacity to deliver H2S, ignite ROS storm, and consumes GSH, all of which enhance ferroptosis susceptibility. This work offers critical insights into leveraging H2S-releasing cascade SAE for potentiating ferroptosis vulnerability in cancer cells.